Damping of Full-Scale Stay Cable with Viscous Damper: Experiment and Analysis. Issue 2 (February 2014) - Zhou, Haijun; Sun, Limin; Xing, Feng
A full-scale cable vibration mitigation experiment was conducted by means of a 215.58-meters-long stay cable attached with a pair of viscous dampers. Test results showed that the damping of the cable was greatly increased after the installation of viscous dampers. It was found that the obtained damping of the cable with viscous dampers depended on the amplitude, and the maximum damping was smaller than the maximum attainable damping. The viscous damper showed nonlinear behaviors regarding the mechanical performances, as well as the interior stiffness. Therefore, the effect of the interior stiffness of a damper on the cable damping was also studied by using an analytical formulation of the complex eigenvalue problem. An engineering approximation concerning the damping of a taut cable with a viscous damper was proposed, where the influence of the interior stiffness was taken into account. The analytical approximate formulations were further extended to nonlinear viscous damper based on the assumption of equivalent energy dissipation in one period. It turned out that the analytical results considering effects of interior stiffness and nonlinearity were in a good agreement with the measured damping. Both the test and analytical results confirmed that damper interior stiffness would greatly reduce the maximum attainable damping, and damping would be amplitude-dependent for cable with a nonlinear viscous damper.